(untitled) (Informatica, 2024)
Since the problems of unsatisfactory performance and long time consumption occur the multimedia image edge detection according to the current image edge detection (ED) method, which makes the multimedia image quality after edge detection not high, to remove the edge features contained in multimedia images efficiently and solve the defects of ignoring the texture of multimedia images in the traditional multimedia image edge detection method, an intelligent monitoring robot-based multimedia image edge detection method is put forward in this paper. The method mainly focuses on the similarity characteristics of pixels and edge detection points between adjacent regions of multimedia images and uses an iterative method to weigh adjacent regions of multimedia images so that the nature of multimedia images is different from the previous traditional images and the improvement of the viewing mode is loved by the audience, who can experience the immersive state and become the subject of the image when watching the movie. The VR images are corrected by binocular offset positioning, and the noise is removed from the updated images, and the 3D edge detection correlation retrieval method is used to obtain the ensemble and outlier values, obtain the maximum/minimum, find out and correct the errors, and calculate the value for completion. The final results of the experiment suggest that multimedia image edge features can be removed by intelligent monitoring robot effectively with the optimal multimedia image edge effect at a high multimedia image processing speed.